PROSES ADAPTASI MAHASISWA RANTAU DALAM MENGHADAPI KOMUNIKASI ANTARBUDAYA (Studi Deskriptif Mengenai Proses Adaptasi Mahasiswa Batam Dalam Menghadapi Hambatan Komunikasi Antar Budaya di UPNVJ) - Rania Putri Faradyba (2022)
Students from Batam go through an adaptation process while dealing with cross-cultural communication at UPN Veteran Jakarta. However, there are barriers to cross-cultural communication in the process since they come from different socio-cultural backgrounds and have no experience with culture in Jakarta. Among everyday life, this causes culture shock in Batam students, creating challenges in adapting and communicating. As a result, the research was conducted employing the Communication Accommodation Theory in order to discover several strategies to adjust in order to adapt successfully at UPN Veteran Jakarta. The study used the qualitative descriptive method using primer and secondary data; the data collecting technique was done by purposive sampling. Then the researcher used the Miles and Huberman data analysis stages which are the data reduction stage, presenting data, then drawing conclusions and verification using the triangulation method. The final result of the study shows that out-of-province students from Batam experienced the five stages of the adaptation process according to Young Y. Kim. Although different, they experienced similar problems in facing cross-cultural communication barriers, which are cultural differences, especially languages, customs, and lifestyle, so they experience culture shock. Therefore, out-of-province students from Batam started to develop in various ways, thus making accommodations and convergence in facing cultural differences to be able to adapt and interact comfortably in the UPNVJ environment.